PEMBERDAYAAN KELOMPOK WANITA TANI NUSA INDAH MELALUI PENGEMBANGAN KEBUN KELOR DAN DIVERSIFIKASI PRODUK OLAHAN KELOR - Masyhuri Majiding, Chaidir; Rozi, Fahrul; Nisaa, Nur Rezky Khairun (Jurnal Abdi Insani, 2025)
Moringa oleifera is a nutrient-rich plant with potential as a functional food and a source of household income. The Nusa Indah Women Farmers’ Group (KWT) has access to moringa resources but faces challenges such as limited knowledge, skills, and the absence of a standardized moringa garden. Consequently, their products have been restricted to sticks and herbal tea, leaving economic value underutilized. Empowerment through training and product diversification was therefore introduced as a strategic solution. This program aimed to enhance the knowledge and skills of KWT Nusa Indah in developing moringa gardens and producing diversified products such as biscuits, dried noodles, and herbal soap. The method included establishing a moringa garden using planter bags, applying compost fertilizer, and conducting training with hands-on product processing. Knowledge was evaluated through pretest and posttest, while skills were assessed by direct observation. The results showed the establishment of a moringa garden with 20 well-maintained plants and the successful production of moringa-based biscuits, noodles, and soap. The mean pretest score of 62.40 increased to 90 in the posttest, with a Wilcoxon test confirming significant improvement (p=0.000). This indicates a 27.6% increase in knowledge. Participants also demonstrated enhanced skills through the ability to produce standardized products. In conclusion, the empowerment program effectively improved knowledge, skills, and productivity of KWT Nusa Indah, while promoting sustainable utilization of moringa as both a nutritional resource and an economic opportunity. Keywords: empowerment, moringa garden, product diversification, women farmers’ group